Towards a phenomenological model for a critical psychotherapy - Gennrich-de Lisle, Peter Hirzel (Rhodes University, Faculty of Humanities, Department of Psychology, 1985)
This thesis aims to establish a model of psychotherapy that is based on experience, but which takes social structure into account. To do this it first sets up a theoretical model of psychotherapy. Thereafter the model is used to analyse four protocols as a way of examining its effectiveness. The analysis of the protocols provides the basis for coming to certain conclusions about the nature of psychotherapy. The theoretical phase first examines the area traditionally known as etiology, but here the approach is from a broadly existential perspective. Thus this section starts by proposing a view of human nature, and then it goes on to say how this nature comes to be disrupted. The influence of the broader social context upon human existence is also considered here. Secondly, there is an attempt to understand how psychotherapy works. Drawing on existential and cultural anthropological material, various themes of psychotherapy are examined, and these are then placed within their social context. Finally, the theoretical phase brings together the themes emerging from the two foregoing sections and integrates them into a single model of "etiology" and "cure". In the following chapter, the adequacy of this model is examined by using it to analyse four protocols written by subjects on their experience of therapy. In the final chapter various conclusions are drawn.
Keywords: Psychotherapy; Phenomenology